Microbial production of polyhydroxyalkanoate (PHA) utilizing fruit waste as a substrate - R, Preethi.; P, Sasikala.; J, Aravind. (Research in Biotechnology, 2013)
Polyhydroxyalkanoates (PHAs) are polyesters of hydroxyalkanoates synthesized by various bacteria as intracellular carbon and energy storage compounds and accumulated as granules in the cytoplasm of cells. PHA producing bacteria from soil were isolated, characterized and screened by Nile blue staining method. Screened organisms were subjected toÃ‚Â fermentation with glucose as carbon source and low-cost raw material like jambul seed (Syzygium cumini). The strain SPY-1 showed higher amount of PHA accumulation when compared to the other strains and was comparable with that of the reference strain Ralstonia eutropha. The extracted PHA granules were analyzed with Fourier transform infrared (FTIR) spectroscopy and the peak was in the regions of 1650.9, 1728-1288 and 1725-1277, correspond to the stretching of the C=O bond which was similar to the standard Polyhydroxybutyrate (PHB).